Deux anomalies segmentaires chez deux especes de Géophilomorphes du Pérou (Myriapoda: Chilopoda) - Demange, Jean-Marie (1980)
Segmental anomalies are described in species of Geophilomorpha, Chilopoda, They are chiefly interpreted by means of the morphology of the trachean system. An "helicomerism" occurs, which tends to a more or less important modification in the morphology of every other segment. Consequently important metameric units, such as appendages, disappear. These anomalies, parallel to the alternate segmenta! reductions of the bi-segmental groupings in Chilopoda, are discussed.